(untitled) (Journal of the College of Basic Education, 2023)
The current study included testing the natural life efficacy of alcoholic tinctures andTincture of vinegar and aqueous extracts of fresh mint leaves as well as mint oilAnd a comparison of its effectiveness with some therapeutic organisms, such as lactic acid bacteria 06140 (01::1:45).] And yeast! twill to assess its inhibition capacityGrowth of bacteria 771077001115 7707215 isolated from urinary tract infections using the methodDisc spread. The results of the primary chemical diagnosis showed that the plant containedActive ingredients such as alkaloids, phenols, tannins, glycosides and flavonoidsand coumarins in alcohol tincture and vinegar tincture with lower results in aqueous extract; And he hasThe results of the study of the inhibitory efficacy of the extracts varied according to the type of the extract itselfAnd the difference of the tested microorganism, as it showed vinegar dye, vinegar alone, and alcohol dyeHigher efficacy in inhibiting bacterial growth than aqueous extract and peppermint oil; and scoredThe highest inhibition rate was 29 mm, 26 mm »24 mm, respectively compared to the diameter of inhibition of bacterialactic acid and Saccharomyces yeast, as the highest inhibition zone was recorded at 6 mm and 3 mm onrespectively, which is less effective for the rate of inhibition of bacterial diameters using plant extracts.